Exposed seronegative: Cellular immune responses to SARS-CoV-2 in the absence of seroconversion - Jay, Cecilia; Ratcliff, Jeremy; Turtle, Lance; Goulder, Philip; Klenerman, Paul (Frontiers in Immunology, 2023)
The factors determining whether infection will occur following exposure to SARS-CoV-2 remain elusive. Certain SARS-CoV-2-exposed individuals mount a specific T-cell response but fail to seroconvert, representing a population that may provide further clarity on the nature of infection susceptibility and correlates of protection against SARS-CoV-2. Exposed seronegative individuals have been reported in patients exposed to the blood-borne pathogens Human Immunodeficiency virus and Hepatitis C virus and the sexually transmitted viruses Hepatitis B virus and Herpes Simplex virus. By comparing the quality of seronegative T-cell responses to SARS-CoV-2 with seronegative cellular immunity to these highly divergent viruses, common patterns emerge that offer insights on the role of cellular immunity against infection. For both SARS-CoV-2 and Hepatitis C, T-cell responses in exposed seronegatives are consistently higher than in unexposed individuals, but lower than in infected, seropositive patients. Durability of T-cell responses to Hepatitis C is dependent upon repeated exposure to antigen – single exposures do not generate long-lived memory T-cells. Finally, exposure to SARS-CoV-2 induces varying degrees of immune activation, suggesting that exposed seronegative individuals represent points on a spectrum rather than a discrete group. Together, these findings paint a complex landscape of the nature of infection but provide clues as to what may be protective early on in SARS-CoV-2 disease course. Further research on this phenomenon, particularly through cohort studies, is warranted.